ChemInform Abstract: Evollionines A—C, Three New Alkaloids Isolated from the Fruits of Evodia rutaecarpa. Issue 19 (May 2015) - Li, Yan‐Hong; He, Juan; Li, Yan; Wu, Xing‐De; Peng, Li‐Yan; Du, Ru‐Nan; Cheng, Xiao; Zhao, Qin‐Shi; Li, Rong‐Tao
Abstract Three new alkaloids, evollionines A (I), B (II), and C (III), are isolated together with two known compounds, evodianinine and wuzhuyumide I.